2011
DOI: 10.18227/1982-8470ragro.v5i2.503
|View full text |Cite
|
Sign up to set email alerts
|

Uso de geoprocessamento na estimativa da perda de solo em microbacia hidrográfica do semiárido brasileiro

Abstract: Resumo-A perda de solo por erosão é um dos problemas ambientais mais sérios da atualidade e tem causado a degradação de vários recursos, principalmente do solo e da água. Objetivou-se com este trabalho, estimar a perda de solos por erosão em uma microbacia localizada no semiárido do Estado do Ceará, efetuada com a combinação de ferramentas de Sistemas Informações Geográficas (SIG) com modelo quantitativo de perda de solo, através da Equação Universal de Perdas de Solos, USLE. A microbacia foi delimitada atravé… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0
16

Year Published

2012
2012
2019
2019

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 3 publications
2
4
0
16
Order By: Relevance
“…However, the author found an increase in the erosive potential between 1976 and 2008, associating the main changes to disorderly land occupation and a reduction in areas with vegetal coverage, which led to silting and changes in the quality of bodies of water. Lopes et al (2011) found a similar pattern in the sub-basin of Varjota Creek in the state of Ceará, Brazil (70.73 km 2 ), in which 74% of the area had soil loss less than 11 t ha -1 year -1…”
Section: Topographic Factor (Ls)supporting
confidence: 60%
“…However, the author found an increase in the erosive potential between 1976 and 2008, associating the main changes to disorderly land occupation and a reduction in areas with vegetal coverage, which led to silting and changes in the quality of bodies of water. Lopes et al (2011) found a similar pattern in the sub-basin of Varjota Creek in the state of Ceará, Brazil (70.73 km 2 ), in which 74% of the area had soil loss less than 11 t ha -1 year -1…”
Section: Topographic Factor (Ls)supporting
confidence: 60%
“…Erosion in these areas is further aggravated by soils of high erosion potential: the Vertisols and the Fluvic Neosol ( Figure 1) Lopes et al (2011), working in the Varjota River watershed in the semi-arid region of the State of Ceará, where they found 74% of the watershed with a mean annual soil loss of less than 11 t ha -1 yr -1 , by the USLE. …”
Section: Resultsmentioning
confidence: 99%
“…Lopes et al (2011) que estimaram as perdas de solo para a bacia do rio Varjota, no semiárido cearense, e encontraram 74% da área da bacia com baixa susceptibilidade a erosão. Os autores atribuíram ao relevo plano a suavemente ondulado e/ou áreas vegetadas os fatores responsáveis pelas baixas taxas de perdas de solo na bacia.…”
Section: Figura 3 Mapa Das Perdas De Solo Na Bacia Do Alto Rio Paraíbaunclassified